Transcriptome Analysis to Understand the Toxicity of Latrodectus tredecimguttatus Eggs - Dehong Xu; Xianchun Wang (Toxins, 2016)
Latrodectus tredecimguttatus is a kind of highly venomous black widow spider, with toxicity coming from not only venomous glands but also other parts of its body as well as newborn spiderlings and eggs. Up to date, although L. tredecimguttatus eggs have been demonstrated to be rich in proteinaceous toxins, there is no systematic investigation on such active components at transcriptome level. In this study, we performed a high-throughput transcriptome sequencing of L. tredecimguttatus eggs with Illumina sequencing technology. As a result, 53,284 protein-coding unigenes were identified, of which 14,185 unigenes produced significant hits in the available databases, including 280 unigenes encoding proteins or peptides homologous to known proteinaceous toxins. GO term and KEGG pathway enrichment analyses of the 280 unigenes showed that 375 GO terms and 18 KEGG pathways were significantly enriched. Functional analysis indicated that these unigene-coded toxins have the bioactivities to degrade tissue proteins, inhibit ion channels, block neuromuscular transmission, provoke anaphylaxis, induce apoptosis and hyperalgesia, etc. No known typical proteinaceous toxins in L. tredecimguttatus venomous glands, such as latrotoxins, were identified, suggesting that the eggs have a different toxicity mechanism from that of the venom. Our present transcriptome analysis not only helps to reveal the gene expression profile and toxicity mechanism of the L. tredecimguttatus eggs, but also provides references for the further related researches.